2005
DOI: 10.1183/09031936.05.00058204
|View full text |Cite
|
Sign up to set email alerts
|

Severity of obstructive airway disease and risk of osteoporotic fracture

Abstract: The use of inhaled corticosteroids has been associated with a dose-related increased risk of fracture. This may be related to systemic absorption. However, several studies have found that patients with more severe reductions in pulmonary function had reduced bone mineral density, independent of inhaled corticosteroids. The objective of this study was to evaluate the relationship between disease severity and fracture risk.A large case-control study (108,754 cases) was conducted using data from the UK General Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
84
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(100 citation statements)
references
References 41 publications
12
84
1
3
Order By: Relevance
“…COPD and bronchial asthma are risk factors for osteoporosis; these patients often display a loss of significant amounts of both cortical and trabecular bone [1][2][3][4][5][6][7][8][9]. These patients are also often treated with oral or inhaled glucocorticoids and this contributes to significant additional bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…COPD and bronchial asthma are risk factors for osteoporosis; these patients often display a loss of significant amounts of both cortical and trabecular bone [1][2][3][4][5][6][7][8][9]. These patients are also often treated with oral or inhaled glucocorticoids and this contributes to significant additional bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…The risk is amplified in patients who are thin (BMI <20 kg/m 2 ; RR, 2.54) and in those who experience exacerbations (RR, 2.02). COPD patients are particularly vulnerable to vertebral fractures [de Vries et al 2005]. Their risk is increased four to eight fold above those without COPD.…”
Section: Osteoporosis and Fracturesmentioning
confidence: 99%
“…Most of the adverse drug effects reported in the studies included in the present review were not severe; nevertheless, some analyses showed arrhythmias, (73) cardiac ischemic events, (74) and fractures. (75)(76)(77) Of those analyses, 21 showed that the adverse effects of COPD medications were worse than were those of placebo. Only 3 analyses-2 involving the use of LAMAs (35) and 1 involving the use of ICs (78) -showed that the medications had fewer adverse effects than did placebo.…”
Section: Adverse Drug Effectsmentioning
confidence: 99%
“…It is possible that the large loss to follow-up among the controls compromised the results and made it difficult to detect that benefit among the patients who received treatment. Two recent meta-analyses compared various therapeutic fracture, (76,77,80) except in one study. (75) However, the use of systemic corticosteroids has been shown to increase that risk.…”
Section: Mortalitymentioning
confidence: 99%